2008
DOI: 10.1002/tox.20430
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin reduces antioxidant defense system and enhances kidney tissue damage in cadmium and lead exposed rats

Abstract: Adrenomedullin (AdM) is synthesized and secreted by a number of cells and tissue. AdM is a potent vasodilator but it is also considered a neuromodulator, an angiogenic factor, and a hormone regulator. AdM possess antiapoptotic, antioxidant, and antimicrobial properties. Heavy metals such as cadmium and lead are found widely in the environment and they have important biological functions. Lead (Pb) and cadmium (Cd) can accumulate in the lungs, liver, bone, and kidneys and cause serious organ damage. In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 50 publications
(43 reference statements)
3
15
0
Order By: Relevance
“…The kidney is one of the most vulnerable organ against the toxic effects of Cd (15). Intoxication of Cd results in common transport defects of the proximal tubules (9,16,17). In the present study, Cd caused severe renal damage in both the aged and young groups.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…The kidney is one of the most vulnerable organ against the toxic effects of Cd (15). Intoxication of Cd results in common transport defects of the proximal tubules (9,16,17). In the present study, Cd caused severe renal damage in both the aged and young groups.…”
Section: Discussionsupporting
confidence: 47%
“…The effects of Cd on various cell types include chromatin condensation and damage to cell membranes, including the mitochondrial cristae membrane, resulting in an increase in their permeability (6). Cd exposure results in the impairment of the antioxidant defense system in the kidney and liver (7)(8)(9). As a matter of fact, the kidney is the most sensitive organ against Cd.…”
Section: Introductionmentioning
confidence: 99%
“…11 Yurekli et al also found that AM significantly decreased MDA levels in kidney tissue after damage in cadmium and lead exposed rats. 12 In this study, AM significantly decreased the renal tissue level of MDA, which indicates that it decreased the magnitude of oxidative stress and subsequently lipid peroxidation. SOD and CT are naturally occurring intracellular enzymes which play a critical role in the defense of cells against the toxic effects ROS products by their scavenging capacity.…”
Section: Discussionmentioning
confidence: 90%
“…In the present study, Pb did not alter any biochemical parameters but damaged the renal structure and reduced the weight in rats (Table and Figure ). This might be due to the different salts of Pb that were used (chloride vs. nitrate) (Yurekli et al ., ). Consistent with our results, the poisoning of Pb damaged the proximal tubular function, which induced histopathological lesions and disturbed the cell integrity (McLachlin, Goyer, & Cherian, ; Navarro‐Moreno et al ., ; Yurekli et al ., ; Martinez‐Alfaro et al ., ; Reddy, Chalamaiah, Ramesh, Balaji, & Indira, ).…”
Section: Discussionmentioning
confidence: 97%